AUTONOMY OF TURKESTAN AND ITS ACTIVITY - Aminov Bakhtiyor Umidovich; Asatov Alibek (Web of Journals Publishing, 2023)
This article examines in detail the first democratic government in the Turkestan Autonomy-Turkistan region, which ruled from November 27, 1917 to February 19, 1918, and the activities carried out during these years.
Keywords: Turkestan Autonomous Region, Ubaidullohoja Asadullohojayev, Hidoyatbek Agayev, Obidjon Mahmudov, Abdurahmon Orazayev, Solomon Gersfeld, O. Mahmudov, Nasirkhan Tora, Saidnosir Mirjalilov, Kokan city, Russia.